Platelets and Microtubules: EFFECT OF COLCHICINE AND D(2)O ON PLATELET AGGREGATION AND RELEASE INDUCED BY CALCIUM IONOPHORE A23187 - Menche, D. (1980)
We examined the role of microtubules in platelet aggregation and secretion (release reaction) induced by the calcium ionophore A23187 (0.8-5 μM). At these concentrations, platelet aggregation was preceded by a lag period of ∼1 min. Colchicine (an agent that disrupts microtubule assembly-disassembly) was shown to bind to platelet microtubules by employing [(3)H]colchicine at a concentration that is specific for microtubules in other tissues (10 nM). Colchicine prolonged the lag period, inhibited the secondary wave of platelet aggregation, and inhibited the release reaction (release of [(14)C]serotonin). Platelets were next incubated with 20-60% D(2)O, an agent that stabilizes microtubules. D(2)O overcame colchicine-induced inhibition of the lag period, aggregation, and release. D(2)O alone enhanced platelet aggregation by 59±14% (SEM) and shortened the lag period by 43±10%. We conclude that functioning microtubules are required for platelet aggregation and release, and that microtubules of platelet preparations are functioning submaximally.